Depression, Anxiety and Stress among Patients with Breast Cancer in Cancer Hospital, Chitwan, Nepal - Shrestha, Nishya; Lawot, Isabel; Tamrakar, Neeta (Journal of Nursing and Health Sciences Nepal, 2024)
Introduction: Patients with breast cancer often experience psychological distress, including anxiety, depression, and potential mood disorders. The objective of the study was to assess the Depression, Anxiety and Stress among patients with breast cancer. Methods: A descriptive cross-sectional study design was used to conduct the study in B.P. Koirala Memorial Cancer Hospital, Chitwan. All patients with breast cancer undergoing treatment at the hospital were taken as study population. Non probability purposive sampling technique was used to select the sample of 111 respondents. Standardized tool DASS-21 was used as research instrument to collect information for Depression, Anxiety and Stress of respondents. Data was entered into Epi-data 3.1 and exported to SPSS- 16 version for data analysis. Descriptive analysis was done to assess the status of Depression, Anxiety and Stress whereas significance of association was measured by using Chi-square test. Results: The mean age of respondents was 46.4 years (range: 23-76). 56.8%, 47.7%, and 40.5% of respondents reported experiencing depression, anxiety, and stress, respectively. Depression was significantly associated with age, educational status, menstrual status, and age at diagnosis of breast cancer (p<0.05), while anxiety and stress were significantly associated with marital status. Conclusions: The study found a high prevalence of depression, anxiety, and stress among patients with breast cancer in BPKMCH. These findings highlight the importance of providing psychosocial support to patients with breast cancer to improve their overall well-being.